Using relief patterns and quartile deviation for modeling of flood susceptibility maps: examples from Presidente Kennedy and Conceição do Castelo, Espírito Santo, Brazil - Raimundo Almir Conceição; Marcelo Eduardo Dantas; Patrícia Mara Lage Simões (Journal of the Geological Survey of Brazil, 2019)
Flood modeling is one of the layers that compose the preliminary susceptibility map, which after the field investigation step is part of the Mass and Flood Movement Susceptibility Map. These maps are produced by the Geological Survey of Brazil, through the National Plan for Risk Management and Response to Natural Disasters (Programa Nacional de Gestão de Riscos e Respostas a Desastres Naturais, PNGRRDN). Initially, the flood modeling methodology consisted of applying the HAND model based on the following variables, hydrographic basin, and soil susceptibility. However, several inconsistencies were observed during fieldwork, especially regarding the model capacity to describe regions with specific hydrological regimes. A methodological improvement using other variables became necessary. Among the proposed variables, the relief susceptibility to floods yielded the most satisfactory results, especially since it could be applied to the entire national territory and was, therefore, introduced to replace the hydrographic basin susceptibility. Furthermore, the methodology used for defining the thresholds of the three flooding susceptibility classes (high, average and low) has also been modified by using the quartile deviation, which provides a less subjective class distribution. Using relief susceptibility and quartile deviation in flood modeling was tested in the Conceição do Castelo and Presidente Kennedy municipalities (Espírito Santo, Brazil), where the morphological configuration covers a wide variety of environments, which is fundamental for the validation of the new variable. The results of the new model were satisfactory. The various types of plains continue to be well represented while a substantial improvement has been observed in the representation of flood-susceptible areas such as marine terraces and colluvium ramps.